Exact Solution of Two-Axis-Twisting Hamiltonian in Bose-Einstein Condensate - Duger, Ulam-Orgikh; Purevdorj, Munkhbaatar (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this Paper, we have dealt with two-axis twisting Hamiltonian for spin squeezing, which is experimentally implementable in Bose-Einstein Condensate, and have found an exact solution by two alternative methods. Many other important nonlinear Hamiltonians could also be solved exactly in a similar way.